Late-Stage Derivatization of Buflavine by Nickel-Catalyzed Direct Substitution of a Methoxy Group via C–O Bond Activation - Shimazumi, Ryoma; Morita, Kosuke; Yoshida, Tomoki; Yasui, Kosuke; Tobisu, Mamoru (Synthesis, 2021)
The nickel-catalyzed cross-coupling of methoxyarenes was applied to buflavine, which allows for the selective monosubstitution of one of the two methoxy groups in the molecule, leading to the formation of 2- and 3-substituted isomers. Trimethylsilylmethyl (TMSCH2), phenyl, and alkynyl groups can be introduced into buflavine using this method. The resulting TMSCH2 analogue of buflavine can also be converted into several other derivatives.
Keywords: C–O bond activation; cross-coupling; nickel; natural product; late-stage functionalization